The acknowledgment of humans rights and them victims the disasters - Guerra da Silva , Érica (Revista da Faculdade de Direito do Sul de Minas, 2018)
This study aims at demonstrating another way to understand human rights through awareness of moral values. To achieve this purpose, this study aimed to theoretical foundation in the Doctrine of Kant, the analysis focused on the victims of disasters resulting from natural events.